DOI: 10.11606/t.5.2014.tde-25112014-150742
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação sequencial do equilíbrio pré e pós-implante coclear em pacientes com surdez pós-lingual

Abstract: professor titular do Departamento de Otorrinolaringologia do HCFMUSP, pela oportunidade de poder realizar essa pesquisa. À minha orientadora Prof. Dra. Roseli Saraiva Moreira Bittar que considero uma verdadeira mentora e um exemplo de profissionalismo. Além disso, possui a admirável capacidade de transformar a complexidade em simplicidade e tem o dom de indicar a pessoa certa para o trabalho certo. Foi um privilégio ter tido a oportunidade de estar ao seu lado e aprender sobre esse universo maravilhoso da Oton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…However, the best postural performance of subjects with AVB can be explained by better use of visual information. It is essential to document the presence of vestibular function before the CI surgery, because it depends on the prognosis of individuals in relation to the skills of learning and postural recovery over time 25 .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the best postural performance of subjects with AVB can be explained by better use of visual information. It is essential to document the presence of vestibular function before the CI surgery, because it depends on the prognosis of individuals in relation to the skills of learning and postural recovery over time 25 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of the twenty-one studies presented, five reported that the preoperative vestibular evaluations can assist in the choice of the side to be implanted. The dysfunction in the pre-surgery moment can be an important risk factor for the CI failure, as well as the choice of the side to be implanted 17,25,[28][29][30] .…”
Section: Literature Reviewmentioning
confidence: 99%